IMC Preferences in BMC School Gresik - KARSTEN, Hadassah Elisha; WONO, Hilda Yunita; HERMAWAN, Jessica Nathalia (International Journal of Environmental, Sustainability, and Social Science, 2024)
In 2021, East Java Province, Indonesia, stood out as a leading provider of education services among the nation's 34 provinces. Private schools, predominant in East Java, surpassed their public counterparts, demonstrating early marketing efforts and innovation. BMC School, situated in Gresik Regency, known as the "City of the Wali Songo," oversees four schools from kindergarten to junior high, emphasizing a Christian foundation and a Theology curriculum. Their annual Admission of New Students program serves as a crucial marketing initiative, employing Integrated Marketing Communications (IMC) strategies such as advertising, digital interactive marketing, personal selling, event marketing, sponsorship, and sales promotion. The research investigates a significant rise in new student enrollments for the 2022/2023 academic year, seeking to determine parents' and guardians' preferred IMC methods. Utilizing a quantitative descriptive approach, the study gathered data through questionnaires, with total sampling involving 70 respondents—parents and guardians who enrolled their children at BMC School Gresik. Survey responses were weighted and averaged, revealing the preferred ranking of IMC activities as interactive digital marketing, event marketing and sponsorship, advertising, and personal selling.